Who Uses Mhealth? User Archetypes for Physical and Mental Health Apps - Maryam Aziz; Aiman Erbad; Samir B Belhaouari; Mohamed B Almourad; Majid Altuwairiqi; Raian Ali (Digital Health, 2023)
Objective This study aims to explore the user archetypes of health apps based on average usage and psychometrics. Methods The study utilized a dataset collected through a dedicated smartphone application and contained usage data, i.e. the timestamps of each app session from October 2020 to April 2021. The dataset had 129 participants for mental health apps usage and 224 participants for physical health apps usage. Average daily launches, extraversion, neuroticism, and satisfaction with life were the determinants of the mental health apps clusters, whereas average daily launches, conscientiousness, neuroticism, and satisfaction with life were for physical health apps. Results Two clusters of mental health apps users were identified using k-prototypes clustering: help-seeking and maintenance users and three clusters of physical health apps users were identified: happy conscious occasional , happy neurotic occasional , and unhappy neurotic frequent users. Conclusion The findings from this study helped to understand the users of health apps based on the frequency of usage, personality, and satisfaction with life. Further, with these findings, apps can be tailored to optimize user experience and satisfaction which may help to increase user retention. Policymakers may also benefit from these findings since understanding the populations’ needs may help to better invest in effective health technology.